Production of biodiesel and analysis of exhaust particulate emissions and metal concentration of lubricant oil of the compression ignition engine - Bhangwar, Sajjad; Liaquat, Ali Memon; Luhar, Muhammad Ramzan; Abbasi, Aijaz; Kumar, Laveet; Rajput, Umair Ahmed; Mastoi, Sanaullah (Frontiers in Energy Research, 2022)
In this research, biodiesel fuel is produced using potassium hydroxide (KOH) as a catalyst and methanol as a co-solvent through the transesterification process. The analysis of particulate matter emissions from a compression ignition (CI) engine with pure diesel fuel (D100), biodiesel-mixed (B30), and clove oil (CL3000 ppm) was carried out. The findings obtained revealed 5.27% reduction of particulate matter in biodiesel-blended fuel, and furthermore, when clove was added to the biodiesel-blended fuel, 11.61% reduction of particulate matter was observed as compared to pure diesel. It may be due to the higher oxygen ratio present in clove oil. The engine was run for 100 h on each fuel sample, and the data were taken and tested per 25 h for elemental analysis. The results manifest that the metal concentration found different elements in lubricant oil, i.e., lead (51.84), (24.89%), and (23.255%); copper (47.41%), (28.71%), and (23.86%); nickel (37.88%), (32.32), and (29.78%); and cadmium (46.12), (29.87%), and (24.01%) in diesel, biodiesel-blended fuel, and biodiesel blended with clove oil, respectively. This study found better results for engine life, which shows the lower metal concentration in biodiesel-blended fuel and clove oil than diesel. Furthermore, the fuels investigated in this research can reduce the wear of engine parts because biodiesel and clove oil contain a high oxygen ratio. Moreover, it has been found that biodiesel and clove oil as an antioxidant have a positive impact on noise emission levels for the CI engine.